Analisis Strategi dan Kendala Guru Biologi Alumni Program Pendidikan Guru Penggerak dalam Implementasi Project-Based Learning (PjBL) di SMA Negeri Kota Jambi - Windy Permata Sari; Ervan Johan Wicaksana; Saparuddin (Mataram University, 2026)
This study aims to analyze the strategies and constraints faced by Biology teachers who are alumni of the Leading Teacher Education Program in implementing Project-Based Learning (PjBL) in Biology learning at Senior High Schools in Jambi City. This study uses a descriptive qualitative approach with a case study design. The main informants consisted of two Biology teachers who are alumni of the Leading Teacher Education Program at Senior High Schools 7 and 8 in Jambi City. Data were collected through in-depth interviews, learning observations, and documentation studies, then analyzed thematically using NVivo 12 Pro. The results showed that the PjBL implementation strategy includes project planning, project management and implementation, learning evaluation and reporting, and experience-based strategies of the Leading Teacher Education Program. The constraints found include student characteristics, school infrastructure and regulations, preparation time, implementation time, conceptual understanding, material suitability and changes in learning patterns, and learning evaluation. The implementation of PjBL is carried out in a planned, adaptive, and student-centered manner, but still requires support for student readiness, facilities, time, material selection, and more systematic evaluation. Future studies are recommended to examine the effectiveness of Project-Based Learning in improving students' learning outcomes, critical thinking skills, and STEM competencies in Biology learning.